2017
DOI: 10.1007/s10291-017-0607-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cycle slip detection method for dual-frequency BeiDou GEO carrier phase observations

Abstract: Cycle slip detection is one of the essential steps for high-precision GNSS data processing when carrier phase observations are involved, such as in precise point positioning (PPP) and precise orbit determination (POD). A number of algorithms have been developed since the 1980s and are effective for processing dual-frequency GPS. However, the emerging BeiDou navigation satellite system in China brings some new challenges for these existing algorithms, especially when small cycle slips occur more frequently. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…The above analysis indicates that, under ionospheric scintillation, using the uniform thresholds such as 1 cycle and 0.05 m can induce a high false-alarm rate of cycle-slips especially using GF combination observable. Similar conclusion is also reported by several previous studies [24,38]. From Figure 5, we may also note that the fluctuation intensity of ∆N MW and ∆Φ GF generally depend on the scintillation level.…”
Section: Conventional Cycle-slip Thresholdsupporting
confidence: 91%
See 1 more Smart Citation
“…The above analysis indicates that, under ionospheric scintillation, using the uniform thresholds such as 1 cycle and 0.05 m can induce a high false-alarm rate of cycle-slips especially using GF combination observable. Similar conclusion is also reported by several previous studies [24,38]. From Figure 5, we may also note that the fluctuation intensity of ∆N MW and ∆Φ GF generally depend on the scintillation level.…”
Section: Conventional Cycle-slip Thresholdsupporting
confidence: 91%
“…Under non-scintillation conditions as ROTI < 0.5 TECU/min or even ROTI < 0.1 TECU/min, we can find some anomalous ∆N MW and ∆Φ GF with large values (|∆N MW | > 3 cycles and |∆Φ GF | > 0.6 m), which show the different characteristic compared to the values presented in Figure 5. Several researchers reported that cycle-slips are easily occurred in GEO carrier-phase measurements compared with IGSO and MEO even under normal ionospheric environment [38,39]. The second and third panels of Figure 6 also support such statement.…”
Section: Cycle-slip Threshold Model Under Ionospheric Scintillationsupporting
confidence: 60%
“…Therefore, the proposed algorithm has a high reliability under ionospheric disturbances. Ju et al (2017) confirmed that due to constant relative position between receivers and BDS GEO satellites, cycle slip often occurs in GEO satellite observables. Since theoretical performance of IGSO and MEO satellites is similar to that of GEO, we only take GEO satellites as an example to test real cycle slip detection and repair performance.…”
Section: Simulated Cycle Slip Detection and Repair Experimentsmentioning
confidence: 55%
“…The first method is called the sample variation method [30], which is to determine the threshold by four times the standard deviation of all the detection values during the observation period. This threshold determination method is simple for calculation and can guarantee a significance level of 0.006%.…”
Section: Determination Of Detection Thresholdmentioning
confidence: 99%
“…The detailed process on how to establish the optimal length can refer to [31,32]. In most cases, the most widely used model GARCH(1, 1) can satisfy the requirement of conditional variance modeling for the detection series [30] because they have a nonzero conditional mean offset and exhibit volatility clustering.…”
Section: Determination Of Detection Thresholdmentioning
confidence: 99%